Joss Whedon, anarchist? a unified theory of the films and television series - Rocha, James 1975-; Rocha, Mona 1977- (Worlds of Whedon, 2019)
"Joss Whedon has provided us with a plethora of TV shows, movies, and one sing-along-blog, all of which shed light on various societal problems through the metaphorical guise of weekly monsters and over-arching big bads. We learn about structural violence through Wolfram & Hart's legal representation of evil; we learn the limits of consent through the Rossum Corporation's coercion and manipulation; we learn about the struggle to locate meaningful freedom from the crew of Serenity; we learn so much from these Whedon-tales. While it has heretofore been difficult to discover a single analytical thread that ties the multiple strings of the Whedonverse together, fortunately and perhaps surprisingly, anarchist theory weaves together many of the major themes that are highlighted in Whedon's oeuvre. All of Whedon's works show various groups of friends, who always unite under love for each other and love for humanity, to undermine hierarchy, whether it is represented by ubersucky vampires, paternalistically sexist watchers, irrepressible law firms, or evil corporations literally hell-bent on bringing about hell on Earth. An anarchist interpretation of Joss Whedon highlights how heroes can come together to act through the force of love to save the world from hierarchy. Again and again."--